Corneal calcification following intensified treatment with sodium hyaluronate artificial tears. Issue 3 (17th February 2006) - Bernauer, W; Thiel, M A; Kurrer, M; Heiligenhaus, A; Rentsch, K M; Schmitt, A; Heinz, C; Yanar, A
Abstract : Aim: To report a potential adverse effect of intensified treatment with sodium hyaluronate artificial tears. Methods: Five cases of deep calcium deposition in the cornea associated with ocular surface disease and frequent use of hyaluronic acid artificial tears are described. All patients used one formulation of phosphate buffered hyaluronate eye drops when rapid calcification developed. All eyes required corneal graft surgery for visual rehabilitation. Specimens at keratoplasty were available for light microscopy and investigation by dispersive x ray analysis. The phosphate concentration in the medication used for topical treatment was measured and compared to alternative hyaluronate preparations. Results: Light microscopy showed dense mineralisation of the entire stroma. The crystalline deposits consisted of hydroxyapatite, Ca5 (PO4 )3 OH. A 50-fold higher concentration of phosphate was measured in the sodium hyaluronate eye drops used for treatment (50.9 mmol/l) when compared with normal serum. The other hyaluronate formulations showed phosphate concentrations from <0.1 mmol/l to 10.9 mmol/l. Conclusions: The hyaluronate artificial tear formulation "Hylo-Comod" favours the formation of insoluble crystalline calcium phosphate deposits in presence of epithelial keratopathy. This is because of its high phosphate concentration and typically frequent instillation. Manufacturers and prescribers should be aware that topical preparations may contain considerable amounts of phosphate which may lead to sight threatening corneal complications.